A Survey on Node Deployment in Wireless Sensor Network (International Journal of Communication Systems and Network Technologies, 2017)
Wireless Sensor Networks (WSNs) expand at a short velocity due to the great collection of programs made accessible by means of this supple technology. One well-known subject with WSNs is power restrictions which can strictly limit network life span. The sensors also have the capability to broadcast and forward sensing data to the base station. Most recent WSNs are bi-directional, permitting two-way communication, which could gather sensing data from sensors to the base station as well as disseminate commands from base station to end sensors. It is used in various areas which are explained in the form of application. In WSN, the deployment of node is the main concept to provide the better communication among the modes. There are many algorithms available for node deployment and in this paper flower pollination optimization used. This method is based on the reproduction of the flower from the movement of pollens from one species to another.
Keywords: Wireless Sensor Network; Node Deployment; Flower Pollination; Self and Cross Pollination